Die räumliche Struktur des Flächenverbrauchs in Deutschland: Eine auf Gemeindedaten basierende Analyse für den Zeitraum 1997 bis 2001 - Siedentop, Stefan; Kausch, Steffen (Raumforschung und Raumordnung | Spatial Research and Planning, 2004)
Next to the quantitative reduction of land consumption, the control of the territorial setting of newly urbanised areas must be acknowledged as a key task of sustainable urban development. Therefore policies against urban sprawl require precise land-use data to inform politicians on the spatial patterns of urbanisation. This article presents an approach for analysing land-use change based on municipality data. For the first time a municipality data base on land-use for the whole territory of Germany has been adopted. The usage of municipality data allows a more sophisticated picture of the patterns of land consumption compared to traditional county-data approaches. The analysis focuses on the spatial concentration of land consumption as well as the distribution of newly urbanised areas among about 13 000 German municipalities.